Streptococcal Pyrogenic Exotoxin F (SpeF) Causes Permeabilization of Lung Blood Vessels - Matsumoto, Masakado (American Society for Microbiology, 1999)
Acute respiration distress syndrome (ARDS) is a typical complication in toxic shock-like syndrome (TSLS) caused by Streptococcus pyogenes. An isolated perfused rat lung model was used to identify the causative agent of ARDS in TSLS in this study. Some crude preparations separated from the culture supernatants of S. pyogenes isolates caused rapid increases in the weight of perfused lungs, indicating vascular permeabilization. Six samples from M type 1 and 3 isolates from TSLS and pharyngitis patients showed strong permeabilization activity, whereas preparations from isolates of other M types (although the number of isolates examined was limited) were negative. The active substance was purified to a single band by sodium dodecyl sulfate-polyacrylamide gel electrophoresis using various columns, and the N-terminal amino acid sequence was determined. The resultant sequence of eight amino acids was identical to SpeF (mitogenic factor). Moreover, the vascular permeabilization activity of the purified band was abolished with anti-SpeF antiserum prepared by immunizing with the purified SpeF. This activity was also neutralized by the antiserum prepared by immunizing with a synthetic peptide derived from the published SpeF sequence. These results suggested that streptococcal SpeF is a major cause of permeabilization of lung blood vessels and sufficient for the pathogenesis of ARDS under the conditions of TSLS caused by S. pyogenes.